Multiple newly identified loci associated with prostate cancer susceptibility. - Eeles, R; Kote-Jarai, Z; Giles, G; Olama, A; Guy, M; Jugurnauth, S; Mulholland, S; Leongamornlert, D; Edwards, S; Morrison, J; Field, H; Southey, M; et al. (2008)
Prostate cancer is the most common cancer affecting males in developed countries. It shows consistent evidence of familial aggregation, but the causes of this aggregation are mostly unknown. To identify common alleles associated with prostate cancer risk, we conducted a genome-wide association study (GWAS) using blood DNA samples from 1,854 individuals with clinically detected prostate cancer diagnosed at